A Type of Coding Method of IPv6 Flow Label with QoS Support - Yangchun Li; Weiwei Feng; Jie Zou; Jinghua Tan (Dianxin kexue)
By redefining the reserved CU bits in IPv6 header traffic class field and the structured code of IPv6 flow label,the region information, application information, port number or other information were defined. The capability of identifying traffic type based on flow label code value was improved, the way to use the IPv6 flow label for differentiated service in IPv6 transiting network was discussed.